EFFECT OF MUROTTAL THERAPY ON BLOOD PRESSURE OF PREGNANT WOMEN WITH HYPERTENSION - Santi Wahyuni; Badriah Badriah; Yanti Cahyati (Journal of Nursing Care, 2021)
The high incidence of cases of Hypertension in Pregnancy (HDK) increases the risk of maternal and perinatal complications, even maternal death. Complementary therapy can be done to help control blood pressure (TD), murottal therapy is one of the therapies that is conceptually believed to provide a relaxing effect that can help control TD. Murottal therapy can be done only by listening to the chanting of the verse (version A), only the translation (B), or the verse accompanied by the translation (C). These types of differences are as far as researchers know that no one has done the research. The purpose of this study was to determine the effect of murottal therapy on changes in BP of pregnant women with hypertension. Quasi-experimental research design with a pretest-posttest group approach. Obtained 27 respondents with inclusion criteria namely Muslims, TD ≥ 140/90 mmHg, and willing to be respondents. The analysis showed that there were differences in systolic and diastolic BP in groups 1, 2, and 3 before and after murottal therapy versions A, B, C, and there were no significant differences between systolic and diastolic BP between the three groups. In conclusion, the three types of murottal therapy performed to have the same effect in reducing systolic and diastolic BP. This shows that any type of murottal therapy has a significant impact in reducing blood pressure. Researchers recommend the application of murottal therapy in HDK patients as an alternative effort to reduce BP.